2001
DOI: 10.1002/ijc.1364
|View full text |Cite
|
Sign up to set email alerts
|

Selective tumor sensitization to taxanes with the mAb-drug conjugate cBR96-doxorubicin

Abstract: The chimeric monoclonal antibody cBR96 conjugated to doxorubicin (cBR96-Dox) is selectively internalized by a wide variety of human carcinomas expressing an extended form of Lewis Y antigen (Le y ). Endocytosis is followed by cleavage and release of free doxorubicin from the endocytic vesicles and subsequent cytotoxicity. Combination studies with standard anti-cancer agents, undertaken to further increase the potency of this targeted therapy, identified significant synergistic anti-tumor activity of cBR96-Dox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Dox appended to other internalizing mAbs can produce a potent G 2 arrest in antigenpositive cells (37). However, treatment with rituximab or rituximab-vcDox at 5 g/mL showed no significant perturbation in cell cycle position or DNA fragmentation compared with untreated control cells, suggesting the free drug was not delivered to the cell interior.…”
Section: Resultsmentioning
confidence: 96%
“…Dox appended to other internalizing mAbs can produce a potent G 2 arrest in antigenpositive cells (37). However, treatment with rituximab or rituximab-vcDox at 5 g/mL showed no significant perturbation in cell cycle position or DNA fragmentation compared with untreated control cells, suggesting the free drug was not delivered to the cell interior.…”
Section: Resultsmentioning
confidence: 96%
“…The Le y antigen is cytophysiologically different from CD33 and CD22 in a sense that internalization of Le y depends on the internalization of the glycoprotein or glycosphingolipid that carries the antigen. Hence, although Le y internalization has been reported for various cell types (22,24), it is difficult to imagine that different cell types would have similar internalization rates for Le y . A different internalization rate could also explain why two cell lines with comparable sensitivity to CalichDMH and expression of Le y (e.g., LNCaP and LOVO; Table 2) still have different sensitivity to hu3S193-Calich-DMH.…”
Section: Discussionmentioning
confidence: 99%
“…However, because Le y is located on the epithelial surface of these tissues, the antigen should have restricted accessibility to administered antibodies (23). In addition, the fact that Le yϪ antibody complexes can be internalized by tumor cells (22,24) further underscores the feasibility of using this TAA as a target for antibody-targeted chemotherapy. To target Le y , an antibody with exclusive specificity to the antigen is ideally required.…”
Section: Introductionmentioning
confidence: 99%
“…suggest that the maximum effect in terms of tumor cell killing is achieved if SGN-15 precedes docetaxel application by 24 h [13]. Additional preclinical work using a nude mouse xenograft model (unpublished data, Seattle Genetics, Inc.) showed that administration of SGN-15 48 h before docetaxel administration led to increased clinical response compared to either concomitant administration of the drugs or administration of docetaxel prior to SGN-15.…”
Section: Discussionmentioning
confidence: 97%
“…Following exposure to doxorubicin, cells arrest in G2 [12] and are then sensitized to G2/M acting drugs such as taxanes. In vitro studies [13] and animal models [14] confirm that the combination of SGN-15 plus a taxane is more effective than either drug alone in several tumor types. Phases I and II studies in subjects with epithelial malignancies, including metastatic breast and colorectal carcinomas, confirm that the combination of SGN-15 and docetaxel is safe and clinically active [15][16][17][18] We now report the results of a randomized Phase II, multicenter study designed to determine the safety and efficacy of SGN-15 and docetaxel in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%